Oxidative stress-induced CDO1 glutathionylation regulates cysteine metabolism and sustains redox homeostasis under ionizing radiation - Yumin He; Dan Li; Hongping Ye; Jiang Zhu; Qianming Chen; Rui Liu (Redox Biology)
Oxidative stress serves as a fundamental mechanism contributing to ionizing radiation-induced damage, which has significant implications for tissue injury. Cysteine dioxygenase type 1 (CDO1) catalyzes the rate-limiting step for cysteine oxidation pathway, thereby playing a crucial role in regulating cellular cysteine availability. However, the regulation of CDO1 activity and cysteine oxidation under ionizing radiation, as well as their subsequent effects on cell viability, remains largely unexplored. In this study, we provide evidence that CDO1 activity and cysteine oxidation are inhibited following radiation exposure. Mechanistically, ionizing radiation-induced oxidative stress triggers glutathionylation of CDO1 at cysteine (C) 164, which impairs CDO1 enzymatic activity by disrupting its interaction with the substrate cysteine. Furthermore, glutathionylation at CDO1 C164 is essential for maintaining cellular redox homeostasis and supports cell viability under ionizing radiation. These findings reveal a novel mechanism through which redox modifications of CDO1 regulate cysteine metabolism and glutathione synthesis under oxidative stress, thereby underscoring its potential as a therapeutic target for addressing radiation-induced injuries.